Britain and the Middle East in the 1930's - Cohen, Michael J. author. aut Link
XVII, 231 p.
Keywords: The chapters in this book focus on the security of the British position in the Middle East between 1935 and 1939. In 1935 Britain was still able to rush reinforcements to the Middle East to forestall hostilities towards Egypt. However, by 1939 the international situation had changed irrevocably.